PENGARUH ECOLOGICAL MARKETING DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP GRADE IMAGE PADA PRODUK TUPPERWARE - Guntur Autura Syanai, Kms; Aninda Safitri, Wahyu; Panorama, Maya; Trisky, Yurini (Penerbit Lafadz Jaya, 2022)
This examination means to figure out the impact of Ecological Showcasing and Corporate Social Obligation on Grade Picture on Tupperware products.The research populace is a buyer client of Tupperware items. Information gathered by conveying polls, the quantity of respondents in this study is 50 respondents. The kind of examination utilized in this study is quantitative exploration with information assortment strategies utilizing surveys. The outcomes showed that Ecological showcasing impacts corporate social obligation, Ecological promoting affects Grade picture, corporate social obligation meaningfully affects Grade picture and Ecological advertising affects Grade picture through corporate social obligation as intervention.